2020
DOI: 10.1007/s12182-020-00473-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of erosion behavior of 304 stainless steel under solid–liquid jet flow impinging at 30°

Abstract: This work carried out liquid-solid two-phase jet experiments and simulations to study the erosion behavior of 304 stainless steel at 30° impingement. The single-phase impinging jet was simulated using dense grid by one-way coupling of solid phase due to its dilute distribution. The simulation results agreed well with experiments. It was found that after impinging particle attrition occurred and particles became round with decreasing length-ratio and particle breakage occurred along the "long" direction. Both e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The simulation results indicated that, as the particle mass loading increases, the effectiveness of plugged tee compared to the standard elbow increases, and influence of particles interaction with flow and particle collision cannot be neglected. Zhao et al (2020) used dense grid by one-way coupling of solid phase to simulate the single-phase impinging jet due to its dilute distribution, and the simulation results agreed well with experiments. These studies have promoted the development of CFD-based erosion prediction technology; however, there is no research on the impact of inter-particle collision on the erosion behavior.…”
Section: Introductionmentioning
confidence: 56%
“…The simulation results indicated that, as the particle mass loading increases, the effectiveness of plugged tee compared to the standard elbow increases, and influence of particles interaction with flow and particle collision cannot be neglected. Zhao et al (2020) used dense grid by one-way coupling of solid phase to simulate the single-phase impinging jet due to its dilute distribution, and the simulation results agreed well with experiments. These studies have promoted the development of CFD-based erosion prediction technology; however, there is no research on the impact of inter-particle collision on the erosion behavior.…”
Section: Introductionmentioning
confidence: 56%
“…The difference between two-way coupling and one-way coupling suggested that two-way coupling did have little effect on the particle distribution for the dilute phase . In this work, the particle volume fraction was α s = 0.5% and very dilute so that one-way coupling was enough to investigate such two-phase flow. , In addition, particle–particle interaction was ignored due to the dilute phase considered . The flow field was simulated and verified to make sure its accuracy and particles were introduced in it.…”
Section: Numerical Modeling Methodsmentioning
confidence: 93%
“…25 the particle volume fraction was α s = 0.5% and very dilute so that one-way coupling was enough to investigate such two-phase flow. 59,63 In addition, particle−particle interaction was ignored due to the dilute phase considered. 64 The flow field was simulated and verified to make sure its accuracy and particles were introduced in it.…”
Section: Numerical Modeling Methodsmentioning
confidence: 99%
“…Broadly and across any research discipline, the description of research design is a prerequisite for producing persuasive representations of research from which readers of research can make sense of new knowledge (Thomson & Kamler, 2012). For instance, written research in the material sciences (see the methodology section of Zhao et al, 2020, for a useful example) tends to include specifications of the materials employed in experiments, ostensibly to allow other scholars to understand, critique, and expand on the research.…”
Section: Establishing Positionalitymentioning
confidence: 99%